ANALISIS IMPLEMENTASI STRATEGI PENYELESAIAN DALAM MEMINIMALISIR PEMBIAYAAN MURABAHAH BERMASALAH (STUDI KASUS BMT AMANAH MADINA) - Syahputra, Andi; Sueb, Mochammad (STIE Bakti Bangsa Pamekasan, 2023)
Analysis of Settlement Strategies in Minimizing Problematic Murabahah Financing at BMT Amanah Madina. Observations and structured data can create solutions in the form of powerful strategies in overcoming all problems in BMT Amanah Madina. BMT Amanah Madina applies several alternatives which I think as a writer are very useful in solving some of the problems that arise in BMT. The settlement strategy depends on the existing problems, and the observation of financial institutions and customers in determining alternative solutions to these problems. The author uses qualitative methods and descriptive approaches in solving his research. By using two data sources, namely primary data obtained by conducting direct interviews with BMT Amanah Madina employees Next is secondary data obtained from references to problematic financing, murabahah financing, journals on problem-solving strategy theory, data on murabahah financing from the internet and previous research. For the purpose of data analysis, researchers use inductive methods in determining the way of thinking from information and data regarding financing mechanisms and customer feasibility analysis about the validation of prospective customers in applying for financing at BMT Amanah Madina. The result of this journal is that there are solutive ways and strategies in dealing with murabahah financing problems and can be used thoroughly by financial institutions that have problems related to problem financing.